PERAN PEMUDA SEBAGAI GENERASI PEDULI LINGKUNGAN DALAM MENINGKATKAN KESADARAN KONSERVASI MELALUI PENDIDIKAN LINGKUNGAN HIDUP - Milandi, Siska Destia; Akbar, Hikmal; Caesar Maeva, Laura Angela (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2025)
The increasing severity of environmental damage highlights the necessity for youth to act as key change-makers in fostering awareness about conservation through environmental education. This research focuses on exploring how young people, as a generation mindful of environmental issues, can enhance awareness of conservation through environmental education. Utilizing a qualitative methodology and a literature review approach, this study gathers information from a variety of pertinent sources. Findings reveal that environmental education is crucial in boosting young people's awareness and understanding of the need for environmental preservation and conservation efforts. For this to be effective, the education must be thorough and continuous, enabling youth to take an active role as educators and promoters of the importance of environmental conservation, as well as leading figures in conservation initiatives.